The Effect of Adding Sargassum sp. Flour to Feed on the Brightness of the Color of Nemo fish (Amphiprion frenatus) - Murtiningsih, Sustanti; Junaidi, Muhammad; Rahmadani, Thoy Batun Citra (Universitas Teuku Umar, 2024)
This study investigates how the addition of Sargassum sp. flour to feed affects the brightness of clownfish color. (Amphiprion frenatus). The experimental method used a completely randomized design (CRD) with five treatments and three replications, resulting in 15 experimental units. The treatments consisting of the addition of Sargassum sp. flour are treatment A (control), treatment B (10%), treatment C (20%), treatment D (30%), and treatment E (40%). Taking three clownfish randomly for each treatment to observe the color development and measure their length and weight every fifteen days on days 0, 15, 30, 45, and 60. Data from observations of color brightness, carotenoid content, and water quality were analyzed descriptively, while data on length and weight growth and survival were analyzed using variance analysis. The research results show that, based on the TCF paper method, Photoshop application, and carotenoid content, the addition of 40% Sargassum sp. flour to the clownfish feed has the greatest effect on the brightness of the clownfish color. There is no significant impact on the survival of clownfish. (Amphiprion frenatus).